1996
DOI: 10.2527/1996.74102523x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide regulation of intestinal glucose absorption.

Abstract: Terminal hydrolysis of oligosaccharides at the small intestinal brush border yields monomeric glucose, most of which is then absorbed by the transepithelial route. This involves carrier-mediated processes requiring specialized functional proteins situated in the brush border (SGLT1) and basolateral (GLUT2) membranes. Glucose translocation at the enterocyte apical membrane is an active, Na(+)-dependent and saturable process, whereas exit from enterocytes is by facilitated diffusion and is energy-independent. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 200 publications
0
24
0
Order By: Relevance
“…Martinez-Sapiña et al (1989) report no changes in intestinal glucose transport in hamsters administered somatostatin. Bird et al (1996a) have reported that subcutaneous administration of somatostatin-14 to mice for 3 d had no effect on 3-0-methylglucose uptake by jejunal rings. If somatostatin has an effect on the absorption of glucose and other nutrients, it is likely an indirect effect via inhibition of gastrointestinal motility and exocrine and endocrine secretion (Krejs 1986;Schusdziarra 1988;Del Valle et al 1990;Mulvihill et al 1990) which has been reported to be mediated by the suppression of synthesis and release of several gut peptides (Schusdziarra 1988;Lewin 1992).…”
Section: Other Peptides and Hormonesmentioning
confidence: 98%
See 1 more Smart Citation
“…Martinez-Sapiña et al (1989) report no changes in intestinal glucose transport in hamsters administered somatostatin. Bird et al (1996a) have reported that subcutaneous administration of somatostatin-14 to mice for 3 d had no effect on 3-0-methylglucose uptake by jejunal rings. If somatostatin has an effect on the absorption of glucose and other nutrients, it is likely an indirect effect via inhibition of gastrointestinal motility and exocrine and endocrine secretion (Krejs 1986;Schusdziarra 1988;Del Valle et al 1990;Mulvihill et al 1990) which has been reported to be mediated by the suppression of synthesis and release of several gut peptides (Schusdziarra 1988;Lewin 1992).…”
Section: Other Peptides and Hormonesmentioning
confidence: 98%
“…This phenomenon is characterized by slowed gastric emptying and intestinal transit when the distal bowel is exposed to unabsorbed nutrients (Taylor 1993). Bird et al (1996a) have reported that PYY increases jejunal glucose absorption in mice without concomitant increase in tissue respiration. This suggests that PYY increases the apparent energetic efficiency of active intestinal glucose transport (Fig.…”
Section: Peptide Yymentioning
confidence: 99%
“…As measured in this study, the energetic component of this term is confounded by the expenditure of ATP for other Na + -dependent transport processes such as amino acids, which are present in the media used in the respiration chambers. In spite of this limitation, previous studies in our laboratory have demonstrated that physiological factors such as age (Bird et al1994b), genotype (Cefalu et al 1998) and exogenous administration of gut peptides such as PYY (Bird et al 1996) can result in changes in this value. Furthermore, studies in our laboratory (Bird et al 1996) and those of others (Schwartz and Storozuk 1988) suggest that induced changes in Na + -dependent carbohydrate transport and Na + -dependent amino acid transport occur in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this limitation, previous studies in our laboratory have demonstrated that physiological factors such as age (Bird et al1994b), genotype (Cefalu et al 1998) and exogenous administration of gut peptides such as PYY (Bird et al 1996) can result in changes in this value. Furthermore, studies in our laboratory (Bird et al 1996) and those of others (Schwartz and Storozuk 1988) suggest that induced changes in Na + -dependent carbohydrate transport and Na + -dependent amino acid transport occur in parallel. However, any change in this ratio may also reflect changes in intracellular metabolism and transport processes of other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of EGF include 1) stimulation of glycolysis in cultured hepatocytes (Schneider et al 1978); 2) triggering of cytosolic alkalinization in chicken granulosa cells (Li et al 1991); 3) increased rate of glucose transport in small intestine (Opleta-Madsen et al 1991;Bird et al 1996); 4) inhibition of Na + transport in rabbit cortical collecting ducts (Vehaskari et al 1991); 5) stimulation of rat jejunal Na + , H + -antiport (Ghishan et al, 1992) and tissue and Na + , K + -dependent O 2 uptake in the small intestine of mice (Bird et al 1994;Croom et al 1998). …”
mentioning
confidence: 99%